2004
DOI: 10.1021/ic049514f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ru(II) Complexes of N-Heterocyclic Carbenes and Their Promising Photoluminescence Properties in Water

Abstract: Novel complexes 1 and 2 based on N-heterocyclic carbenes, which are analogous to Ru(bpy)(3)(2+) and Ru(terpy)(2)(2+), respectively, were synthesized. The complex, which is analogous to Ru(terpy)(2)(2+), exhibited promising photoluminescence properties with a long lifetime of 820 ns in acetonitrile and 3100 ns in water at room temperature, respectively. In addition, ab initio calculations were carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
71
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(75 citation statements)
references
References 53 publications
4
71
0
Order By: Relevance
“…Since no structural data was reported for the first Ru(III)-NHC complex RuCl 2 (PPh 3 )[OCPh(CH 2 {1-C[NCHCHNBu t ]}) 2 ] [35] and no Os(III)-NHC complex is known, there is no reported Ru(III)/Os(III)-NHC bond length for comparison with those in 1a and 1b. Interestingly, the metal-NHC bond lengths in 1a and 1b are comparable with those reported for Ru(II) or Os(II)-NHC complexes [44][45][46][47][48][49].…”
supporting
confidence: 80%
“…Since no structural data was reported for the first Ru(III)-NHC complex RuCl 2 (PPh 3 )[OCPh(CH 2 {1-C[NCHCHNBu t ]}) 2 ] [35] and no Os(III)-NHC complex is known, there is no reported Ru(III)/Os(III)-NHC bond length for comparison with those in 1a and 1b. Interestingly, the metal-NHC bond lengths in 1a and 1b are comparable with those reported for Ru(II) or Os(II)-NHC complexes [44][45][46][47][48][49].…”
supporting
confidence: 80%
“…The lower-energy bands, which are sensitive to substituent effects on the pyridine ring, are ascribed to the dp(Ru)!p*-A C H T U N G T R E N N U N G (NHC-py) metal-to-ligand charge-transfer (MLCT) transitions, similar to that observed in the related [RuA C H T U N G T R E N N U N G (NHCpy) 3 ] 2 + complex. [15] The substituents on the pyridine ring are found to tune the electronic absorption energy of the complexes in a trend of CF 3 < H < 4-OMe, in line with the substituent effect generally observed in MLCT transitions (Figure 1a). Moreover, the low-energy band has been found to show a large blueshift upon addition of acid to methanolic solutions of the complexes, which is characteristic of a number of cyano-containing ruthenium(II) complexes, [16] and strongly suggests the MLCT nature of the transition ( Figure 1b).…”
supporting
confidence: 72%
“…[6][7][8][9][14][15][16][17][18] A steady growth of interest in Ru(II)-NHC anticancer drugs and photoluminescence study of Ru(II)-NHC complexes over the last 20 years is reflected in the accelerating growth of publications. [13,[19][20][21][22][23] Interestingly, Ru anticancer drugs have been growing rapidly since NAMI-A (ImH+)[RuIIICl4(Im) (S-dmso)], where Im = imidazole and S-dmso = S-bound dimethylsulfoxide) or KP1019 (IndH+)-[RuIIICl4(Ind)2], where Ind = indazole, has successfully completed phase-I clinical trials and an array of other Ru complexes have shown promises for future development. [21] Several metals, Cu(I), Ag(I), Au(I), Au(III), Pd(II), Pt(II)-NHC are reported as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%